Why Has the Socialism of Sumak Kawsay/Good Living Failed as a New Revolutionary School of Thought in Latin America? - Aurelio García-García (Revista Mexicana de Ciencias Políticas y Sociales)
Sumak kawsay socialism, or good living socialism, is one of the three schools of political thought of sumak kawsay which first appeared in the first decade of the twenty-first century. The idea of good living is currently re-emerging in debates on how to build a new post-pandemic world. Sumak kawsay socialism, however, has remained on the sidelines of the political landscape and academic discussions. In its place, twenty-first century socialism has once again reappeared as the socialist proposal to create and organize a new system. This paper will analyze which practical and theoretical weaknesses and contradictions have led to the disappearance of good living socialism from political and intellectual debates. It concludes that intellectuals from different branches of socialism used sumak kawsay/good living as a “key symbol” to take advantage of the social, economic, political, and environmental situation in Ecuador and Bolivia in order to seize power.